Year of fulfilment : 20 point programme (Directorate of Advertising & Visual Publicity, Ministry of I. & B., Govt. of India, 1976)
On the economic programs of the Indian Prime Minister Indira Nehru Gandhi, b. 1917, and the achievements of national emergency declared on June 26, 1975.